A standardized imaging protocol improves quality and reduces practice variability in echocardiographic assessment of ventricular function by first‐year pediatric cardiology fellows. Issue 8 (5th August 2019) - White, Brian R.; Ho, Deborah Y.; Rogers, Lindsay S.; Natarajan, Shobha S.
Abstract: Background: Echocardiography education for pediatric cardiology fellows has been a recent focus leading to the implementation of "boot camps." Less is described about continuing education through fellowship and improving image quality. We noticed practice variation in echocardiograms assessing ventricular function performed on nights and weekends. Thus, we implemented a standardized protocol and assessed its impact on imaging and reporting completeness. Methods: We created an imaging protocol for the assessment of ventricular function in the acute setting. The protocol included demographic information, a list of images to be obtained, and the methods to quantify ventricular function. The protocol was explained to first‐year fellows and distributed on an electronic quick reference card. Echocardiograms independently performed by first‐year fellows during their first 4 months of on‐call time were assessed pre‐ and postintervention using a standard rubric. Results: Compliance with demographic reporting was high pre‐ and postintervention, but significantly improved after the standardized protocol ( P  <   0.001). Use of the protocol increased the median number of unique images obtained per echocardiogram from 13 to 17 (out of 23 required views, P  <   0.001). Particularly improved was the performance of quantitative evaluations of function, including Simpson's method for left ventricular ejection fraction (four chamber: 40% vs 67%, P  <   0.001; two chamber: 33% vs 67%, P  <   0.001) and tricuspid annular plane systolic excursion (45% vs 80%, P  <   0.001). Conclusions: The introduction of a standardized imaging protocol and its distribution to first‐year fellows resulted in improvements in echocardiographic reporting completeness and increased the quality of information obtained by providing more quantitative assessments of ventricular function.